2019
DOI: 10.1016/j.bpsc.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Morphometry in the Psychosis Risk Period: A Comprehensive Perspective of Surface Features

Abstract: Background-Gyrification features reflect brain development in the early prenatal environment. Clarifying the nature of these features in psychosis can help shed light on the role of early developmental insult. However, the literature is currently widely discrepant, which may reflect confounds related to formally psychotic patient populations or overreliance on a single cortical surface morphometry(CSM) feature. Methods-The present study compares CSM features of gyrification in clinical high-risk (CHR, n=43) yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 56 publications
2
13
0
Order By: Relevance
“…We also found that ultra-high risk individuals showed reduced cortical complexity in the superior temporal gyrus (STG) and insula in the left hemisphere, corresponding with previous studies that found differences of gyrification in UHR (23). STG and insula are essential for auditory perception, cognitive functions, thought and language processing.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We also found that ultra-high risk individuals showed reduced cortical complexity in the superior temporal gyrus (STG) and insula in the left hemisphere, corresponding with previous studies that found differences of gyrification in UHR (23). STG and insula are essential for auditory perception, cognitive functions, thought and language processing.…”
Section: Discussionsupporting
confidence: 88%
“…These studies have shown subtle cortical folding abnormalities in neocortical areas overlapping with those seen in VBM studies of schizophrenia ( 20 22 ). More recently, abnormalities of cortical surface features have also been shown in clinical high-risk youth with a prodromal syndrome ( 23 ). However, it remains unclear whether early environmental stressors like childhood trauma might interact with other (e.g., genetic) factors resulting in abnormal surface morphology.…”
Section: Introductionmentioning
confidence: 99%
“…A few MRI studies on cortical surface features in clinical high-risk individuals also showed similar gross morphological characteristics, such as altered sulcogyral patterns (Sasabayashi et al, 2017;Nakamura et al, 2019) and sulcaldepth abnormalities (Takahashi et al, 2019b), with patients with established Sz. In contrast to the evidence of active gray matter reductions in the superior temporal plane (e.g., HG and planum temporale) during the early illness stages of psychosis (Takahashi and Suzuki, 2018), a recent longitudinal study demonstrated the stability of gyrification features during the clinical high-risk period as a marker of early neurodevelopmental insults (Damme et al, 2019). Nevertheless, high-risk individuals with the later onset of psychosis may exhibit greater gyrification abnormalities before illness onset (Sasabayashi et al, 2017;Das et al, 2018) because greater and/or more prolonged neurodevelopmental deviations during gestation and consequent anomalous postpubertal brain changes may lead to overt and sustained psychosis (Pantelis et al, 2005).…”
Section: Discussionmentioning
confidence: 88%
“…Second, this cross‐sectional study could not directly elucidate the trajectories of the gyrification pattern. The cortical folding pattern is assumed to be genetically mediated and remains rather stable across adolescent neuromaturational processes in both HC and high‐risk individuals . However, a progressive LGI reduction was also demonstrated in schizophrenia patients, which may be due to gray matter volumetric reduction overtime .…”
Section: Discussionmentioning
confidence: 99%